Experimental soil dynamic force: An improvement of Standard Penetration Test (SPT) interpretation - Lukiantchuki, J. A.; Bernardes, G. P.; Esquivel, E. R. (My University, 2013)
The Standard Penetration Test (SPT) is widely used for geotechnical subsurface investigation. It is intended to provide soil properties and foundation design parameters. Schnaid et al. (2009) proposed a rational method to assess the dynamic force (F d), corresponding to the dynamic soil reaction to the sampler penetration, based on the amount of energy delivered to the sampler. This paper presents the results of SPT tests performed with two instrumented subassemblies, one placed at top and the other one at the bottom of the string of rods. This instrumentation allowed the assessment of the amount of energy transmitted to the string of rods, at sections just below the anvil and just above the sampler. Also, dynamic soil reaction forces were estimated through measurements of normal forces at a section just above the sampler. These reaction forces were then compared to the dynamic reaction forces estimated using the equation proposed by Schnaid et al. (2009). Results showed that experimental dynamic reaction values are lower than theoretical ones. However, it is possible to correct theoretical values using a multiplying factor, which can be evaluated from the amount of energy at top and bottom of the string of rods.
Keywords: Energy; Soil dynamic reaction force; SPT; Standard penetration test